THE INVERSION METHOD OF FOUR-BIT BOOLEAN SAC CRYPTOTRANSFORMS - Fedotova-Piven, I. M.; Rudnytskyi, V. M.; Piven, O. B.; Myroniuk, T. V. (Radio Electronics, Computer Science, Control, 2019)
Context. Nonlinear systems of Boolean functions play a prominent role in the protection of cryptosystems. The creation and use of new four-bit cryptographic transformations with nonlinear Boolean functions that have the property of strict avalanche criterion is an actual task for increasing the reliability of information protection systems. Objective. The goal of the work is creating a method for obtaining inverse four-bit cryptographic transformations with the strict avalanche criterion property, which contain balanced Boolean functions only with the operations of inversion and addition modulo two. Method. A method is proposed for obtaining inverse four-bit cryptographic transformations with the strict avalanche criterion property, each of which contains balanced Boolean functions only with the operations of inversion and addition modulo two. The method simplifies the process of finding inverse cryptographic transformations by creating a class of thirty balanced basic Boolean functions with the required predefined limitations and properties and for finding, within this class, the basic Boolean functions that make up the inverse cryptographic transformation. Results. The effectiveness of the method is shown for obtaining two inverse four-bit cryptographic transformations with the property of a strict avalanche criterion from two direct four-bit cryptographic transformations with the property of a strict avalanche criterion. Conclusions. For the first time, there was proposed a method for obtaining inverse four-bit cryptographic transformations with the strict avalanche criterion property for balanced Boolean functions containing two logical operations (inversion and addition modulo two) to ensure reliable information protection. This method is a method of selecting the already existing basic Boolean functions from a predetermined set of balanced basic Boolean functions for direct and inverse cryptographic transformations, whereas the existing methods of searching for inverse cryptographic transformation are methods for calculating each element of the Boolean functions for the inverse cryptographic transformation. The method can be extended to a larger even number of arguments of the balanced Boolean functions of cryptographic transformations to increase the cryptographic resilience.